ANALISIS PENANGANAN KREDIT BERMASALAH PADA BANK PERKREDITAN RAKYAT CABANG RIMBA MELINTANG ROKAN HILIR - Nurul Haflah; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to identify and analyze non-performing loans at the Rokan Hilir People's Credit Bank, Rimba Melintang Branch, 2015-2019. This study uses secondary data in the form of data obtained by the author through manual reports and financial reports obtained from the Rokan Hilir People's Credit Bank, Rimba Melintang Branch, which is needed by researchers for the analysis of non-performing loans. This research use desciptive qualitative approach. Data collection is obtained from interviews with banks and debtors. Checking the validity of the findings using source triangulation so that it is easy to analyze various problems that occur in the company. The conclusions of this study are (1) factors from debtors and internal factors that cause non-performing loans at Rokan Hilir People's Credit Bank, Rimba Melintang Branch (2) the handling of problem loans that have been implemented is routine collection, credit restructuring.  Keywords: non-performing loans, handling of problem loans